Molecular characterization of human T cell leukemia virus type 1 subtypes in a group of infected individuals diagnosed in Portugal and Spain - Pádua, Elizabeth; Rodés, Berta; Pérez-Piñar, Teresa; Silva, Ana Filipa; Jiménez, Victoria; Ferreira, Filipa; Toro, Carlos (AIDS research and human retroviruses, 2011)
Over the past decade, Portugal and Spain received large numbers of immigrants from HTLV-1 endemic areas. Our aim was to investigate the diversity of subtypes circulating in these two countries and the introduction of new variants. We performed a molecular analysis of HTLV-1 strains in patients diagnosed since 1998. LTR and env proviral sequences from 26 individuals were analyzed to generate phylogenetic trees along with reference HTLV-1 subtypes from several geographic origins. Epidemiological and clinical data were recorded. Most subjects were immigrants (57.7%) from South America and Africa. All isolates belonged to the cosmopolitan A subtype. Most carried the transcontinental subgroup A, but five subjects carried subgroup D and one carried subgroup C, previously unreported in Europe. HTLV strains showed separate clusters linked to the patients' geographic origin. Although subjects with HTLV-1 infection tend not to be engaged in high-risk practices, silent dissemination of a broad diversity of HTLV-1 viruses may still occur.